The Apocryphal Acts of the Apostles : An Introduction - Klauck, Hans-Josef (Book collections on Project MUSE., 2008)
The book discusses both the main apocryphal Acts, such as the Acts of John, Paul, and Peter, and the more recent works, including the Acts of Philip, Bartholomew, and Matthew. For each chapter Klauck offers a explanation of the background and the structure for each of the works presented, and a detailed analysis of the content, and a bibliography all while incorporating the results of the most current international research. --From publisher's description.